(untitled) (Philological Studies, 2019)
The paper shows the processes terminologization, retreminologization and determinologizatioan in the Macedonian standard language. The research has qualitative paradigm and descriptive design. The sample consists of lexical units form the common language, as well as from various scientific and technical areas, excerpted from the everyday interactions of the native Macedonian speakers. The methods used for processing the data and gaining conclusions are analysis, synthesis and comparison. The research shows the semantic and grammatical potentials of the analyzed lexical units that are result of the already mentioned processes.